Investigation of the relatıonshıp of palatal arch morphometry with maxillary sinus volume: CBCT study - Tassoker Melek; Öztürk Büşra; Aydin Kabakçi Anil Didem (Balkan Stomatological Society, 2024)
Background/Aim: The maxillofacial region is a complex of anatomical structures that are in close proximity and connection with each other. The aim of this study was to determine the shape, depth, width, length and palatal vault angle of the palatal arch on cone beam computed tomography (CBCT) images taken for various reasons and to determine the relationship between these factors and maxillary sinus volume. Material and Methods: CBCT images of a total of 150 male and female patients over the age of 18, taken for different diagnostic purposes, were evaluated by an oral radiologist with two years of experience. The shape of the palatal arch was determined on each image, and palatal depth, width, length and palatal vault angle were measured. ITK-SNAP (version 3.8.0) software was used for maxillary sinus measurement. Statistical analysis of the study was performed using SPSS v.21 software. Results: All of the measured parameters were found to be statistically significant between genders, except for the palatal vault angle. As a result of the correlation analysis, it was shown that palatal length was 0.4% (R2=0.004), palatal depth was 42.3% (R2=0.423), and palatal width was 2%(R2=0.020) effective in explaining the palatal vault angle. A high level of correlation was detected between the right (1) and left (2) sinus maxillaris volumes and total sinus maxillaris volumes (r1=0.959, r2=0.961). Conclusions: There is a significant difference in palatal arch parameters between different genders. In addition, these dimensions also play a role on maxillary sinus volumes.